Increase in the cervical length after the loop electrosurgical excision procedure for grade III cervical intraepithelial neoplasia. (2nd January 2017) - Chikazawa, Kenro; Netsu, Sachiho; Akashi, Keiko; Suzuki, Yurina; Konno, Ryo; Motomatsu, Shigeru
Abstract: This study aimed to determine whether the cervical length increases over a period of six months, after the loop electrosurgical excision procedure (LEEP) for grade III cervical intraepithelial neoplasia (CIN), and to identify the factors associated with an increase in the cervical length. We retrospectively reviewed the medical records of 183 patients who underwent the LEEP between April 2011 and March 2014, at the Department of Gynaecology, Kyosai Hospital. Transvaginal ultrasonography was performed at two, three and six months after the LEEP, and the mean increase in the cervical length between two and three months, two and six months, and three and six months were 2.07, 5.23 and 2.92 mm, respectively. The increase in the cervical length was not associated with age, gravidity, parity and the width of CIN. In conclusion, the cervical length may increase gradually over a period of six months after the LEEP.